The Impact of Aging on the Function of Retinal Ganglion Cells - Prinz, Julia; Walter, Peter; Liu, Hanhan; Prokosch, Verena (Klinische Monatsblätter für Augenheilkunde, 2024)
Aging is a major risk factor for retinal neurodegenerative diseases. Aged mammalian retinal ganglion cells (RGCs) lack the ability to regenerate axons after injury. Rodent models suggest that older age increases the vulnerability of RGCs to injury and impairs RGC function as well as their functional recovery. Molecular changes – including decreased circulating levels of brain-derived neurotrophic factor (BDNF) – might contribute to impaired RGC dendritic extension during aging. Moreover, age-related mitochondrial dysfunction plays a major role in aging processes, as it leads to reduced adenosine triphosphate and increased generation of reactive oxygen species. Autophagy activity is necessary for the maintenance of cellular homeostasis and decreases with aging in the central nervous system. During aging, vascular insufficiency may lead to impaired oxygen and nutrient supply to RGCs. Microglial cells undergo morphological changes and functional impairment with aging, which might compromise retinal homeostasis and promote an inflammatory environment. Addressing these age-related changes by means of a low-energy diet, exercise, and neurotrophic factors might prevent age-related functional impairment of RGCs. This review focuses on the current understanding of aging RGCs and key players modulating those underlying mechanisms.
Keywords: retinal ganglion cells; aging; retina; optic nerve; glaucoma